2021
DOI: 10.3389/fnins.2021.734158
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Function Is Impaired by a Short-Term High-Fat Diet in Mice: Increased Blood–Brain Barrier Permeability and Neuroinflammation as Triggering Events

Abstract: Graphical AbstractAn illustrative scheme summarizing the main outcomes in Swiss mice fed high-fat diet (HFD), with their exact time of onset of changes in the hippocampus. An increase in the expression of proinflammatory cytokines, together with the permeability of the blood–brain barrier was detected after 2 days of HFD. Even in the first week of dietary intervention, memory and learning impairment, depressive-like behavior, and synaptic changes were observed at 3, 5, and 7 days, respectively. Later hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 58 publications
3
72
2
1
Order By: Relevance
“…Yang and colleagues observed that the excess of lipid intake from diet diminishes mitochondrial biogenesis and alters fusion- fission protein levels in hippocampus of mice (Yang et al, 2021). We also verified a reduced hippocampal mitochondrial function in adult mice fed a HFD (de Paula et al, 2021). Furthermore, BAT mitochondrial metabolism has currently gathered attention as a therapeutic target for obesity and related metabolic disorders (Lettieri Barbato et al, 2015; Tseng et al, 2010).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Yang and colleagues observed that the excess of lipid intake from diet diminishes mitochondrial biogenesis and alters fusion- fission protein levels in hippocampus of mice (Yang et al, 2021). We also verified a reduced hippocampal mitochondrial function in adult mice fed a HFD (de Paula et al, 2021). Furthermore, BAT mitochondrial metabolism has currently gathered attention as a therapeutic target for obesity and related metabolic disorders (Lettieri Barbato et al, 2015; Tseng et al, 2010).…”
Section: Introductionmentioning
confidence: 58%
“…A recent study from our group reported memory dysfunction in adult Swiss mice as early as 3 days after HFD introduction (de Paula et al, 2021). Interestingly, some studies emphasize that behavior and metabolic changes are more intense when HFD is introduced earlier in life.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that energy-dense food consumption triggers severe health conditions such as metabolic syndrome, cardiovascular disorder, neurovascular dysfunction, memory deficits, as well as AD ( Thériault et al, 2016 ; Ting et al, 2017 ; Moreno-Fernández et al, 2018 ; Lasker et al, 2019 ; Bracko et al, 2020 ). Studies in animals fed with short-term or long-term enriched-energy diet increased the permeability of the BBB as demonstrated by an elevation of extravascular immunoglobulin G deposits and albumin content in the hippocampus ( de Aquino et al, 2018 ; Yamamoto et al, 2019 ; de Paula et al, 2021 ). Animals fed with a high-calorie diet exhibited attenuation of tight junction proteins claudin 5 and occludin, alleviation of collagen type IV, augmented fenestration of endothelial cells, and astrogliosis ( de Aquino et al, 2018 ; Yamamoto et al, 2019 ).…”
Section: Vascular Risk Factors Linked To Alzheimer’s Diseasementioning
confidence: 99%
“…Additionally, Alabamians with less education ( Figure 2A ) and low income ( Figure 2B ) were more susceptible to diabetes ( Explore Diabetes in Alabama, 2021 Annual Report). Several studies have shown an association between diet-induced obesity or diabetes with vascular dysfunction ( Chang et al, 2014 ; de Paula et al, 2021 ; Li et al, 2021 ). Excessive caloric consumption stimulates peripheral immune cells, induces the generation of proinflammatory cytokines and increases oxidative stress, which have all been linked to BBB dysfunction ( Salameh et al, 2019 ).…”
Section: Vascular Risk Factors Linked To Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation